Potentiality of Bamboos to Combat Climate Change Impacts and Biodiversity Conservation in the Annapurna Conservation Area, Nepal - Ghale, Kabita; Yadav, Shailendra Kumar; Thapa, Neeru; Sah, Jit Narayan (Journal of Forest and Natural Resource Management, 2020)
Diverse physiography and topography have made the landscape of Nepal fragile and highly vulnerable to climate change. Bamboo is likely to be highly able to stock carbon due to its rapid and easy growth. Here we explore the potentiality of bamboo to combat climate change impacts and biodiversity conservation through mitigation. The mitigation potentiality is studied through biomass and biomass carbon estimation along with soil carbon estimation. Data collected through participatory resource mapping, direct field observation and biophysical measurements were analyzed for biomass estimation and carbon stocking in the biomass and soil of bamboo stand, using Statistical analysis. The study revealed that Melocanna baccifera yielded the highest potential biomass carbon density of 109.41 tons C/plot, followed by Bambusa Nepalensis and Himalayacalamus Fimbriatus of 85.10 tonsC/plot and 64.58 tons C/plot, respectively. However, the soil under Himalayacalamus fimbriatus yielded the highest potential soil organic carbon of 49.24 tons C/plot, followed by the soil under Bambusa Nepalensis and Melocana Bacifera of 38.69 tons C/plot and 27.91 tons C/plot, respectively. Unsustainable extraction of bamboo was highly threatening, therefore, conservation education is recommended to aware local people of the importance of bamboo having the potential to fight against climate change and bringing harmony between biodiversity conservation and traditional culture is recommended.